Contract law for dummies - Burnham, Scott J.; Kraynak, Joe. (Hoboken, N.J. : John Wiley & Sons, 2012)
Take the mumbo jumbo out of contract law and ace your contracts course. This hands-on guide give you plain-English explanations of terminology and language used in contracts, showing you how to read and analyze cases and statues with ease.
Introducing contract law and contract formation -- Determining whether a contract is void, voidable, or unenforceable -- Analyzing contract terms and their meaning -- Performing the contract or breaching it -- Exploring remedies for breach of contract -- Bringing third parties into the picture -- The part of tens.
Includes index.
Keywords: Contracts